The future of OMFS lies in creating pathways to implement the PMETB recommendations and inspiring our trainees. Enough time has been spent debating, we need to deliver!: Re: Newman L, Brown J, Kerawala C, et al. Our specialty. The future. Is the writing on the wall? Br J Oral Maxillofac Surg 2020 (online ahead of print). Issue 10 (December 2020) - Bentley, R.; Parmar, S.; Smith, A.; Dhariwal, D.K.; Banks, R.; Keith, D.; Brennan, P.A.; Magennis, P.
Abstract: The British Association of Oral and Maxillofacial Surgeons (BAOMS) has been at the centre of the transition of our specialty in the UK from a branch of dentistry to one of the 10 UK surgical specialties. In this role it has, at different times, pushed boundaries against resistance from other specialties, and redirected the ambitions of the deputy chair of the Postgraduate Medical Education and Training Board (PMETB) review to produce recommendations that were exactly what OMFS needed. The editorial Our specialty. The future. Is the writing on the wall? is just the most recent iteration of half a century of internal debate. Whilst there are some issues with how the authors have presented recruitment data (their figures omit ST1 run-through and do not recognise that the same single, unfilled post may be present for two or more national selection rounds) their first paragraph A debate that we feel is long overdue presents the greatest concern. In this short communication, we illustrate that in the last 20 years the specialty has not been short of debate. In the absence of new and specific evidence that any other route forward would be supported by our national training committee (OMFS SAC), our regulator (GMC), the breadth of our specialty (including our current specialists and our current and future trainees) and, most importantly, would actually address our problems, we should avoid putting energy into an empty debate. Our focus should be on delivering the PMETB recommendations and inspiring our future trainees.